Critique on “Projectile Motion Analysis in the Presence of Dissipative Forces for the High Speed Regime” [Rev. Bras. Ens. Fis. 45, e20230060 (2023) - Mendrot, Vitor B. [UNESP]; de Castro, Antonio S. [UNESP] (FapUNIFESP (SciELO), 2023)
We have examined the recent publication titled “Projectile Motion Analysis in the Presence of Dissipative Forces for the High Speed Regime” [Rev. Bras. Ens. Fis. 45, e20230060 (2023)] and identified an extremely unfortunate mistake in the equations of motion used for projectile motion. The correct formulation involves a set of coupled nonlinear differential equations that are well-established in the literature. Our findings indicate that incorporating linear drag in speed, alongside the independent horizontal and vertical motions governed by decoupled linear equations, offers a more pedagogical representation of the impact of drag forces on the trajectory and overall dynamics of moving objects, especially in undergraduate introductory courses.
Keywords: Drag force; Equations of motion; Projectile motion